896-P: Positive Effect of Acute and Chronic Effects of Oral Ketones in Subjects with HFrEF and Diabetes - ACOSTA, FRANCISCA M.; CHIDURALA, SUCHIT; FRAUSTO, PAOLA; MARQUEZ NAJERA, GUILLERMO; MOODY, ALEXANDER; TODD, BYRON; HU, BEVERLY; ROLLINS, CAITLYN; JUAREZ, DEANNA; ESCOBAR VASCO, MARIA; CLARKE, GEOFFREY D.; SOLIS-HERRERA, CAROLINA (Diabetes (New York, N.Y.), 2025)
Introduction and Objective: Ketones are energy substrates, serving as a "superfuel" for the heart, skeletal muscle, etc.. Our previous work showed that 3-hour intravenous (IV) exogenous ketones (KE) improved left ventricular function in T2D patients with HFrEF by up to 6%, dose-dependently. However, IV delivery is invasive and impractical for daily use. This study explores acute (3-hour) and chronic (1-week) effects of oral ketones on heart function in T2D patients with HFrEF. Methods: 8 participants with T2D (BMI 23-38 kg/m², HbA1c 6.0-10.0%, eGFR ≥30 ml/min/1.73m², EF <50%) were included. Baseline assessments included a 6-minute walk test (6MWT) and PROMIS Physical Function (PPF) survey. In the acute study, participants consumed two doses of DeltaG-ketone monoester 90 mins. apart. Cardiac MRIs and blood tests were performed pre- and post-dosing. In the chronic study, participants repeated daily ketone dosing for 7 days, with final assessments on day 8. Results: Blood ketone levels significantly increased during the acute phase, peaking at 6±0.3 mmol/L after 3 hours (p<0.0001), without significant changes in glucose (p=0.23). Ejection fraction (EF%) improved significantly during the acute phase (5.0±1.3%) and after 7 days of daily dosing (4.9.±0.6%). Conclusion: Oral KE ingestion shows promise as an adjunct therapy for T2D patients with HFrEF, potentially reducing acute HF admissions and improving mortality. Larger studies are needed to validate these findings.